Determinants of Women’s Leadership Position: A Case of Women Entrepreneurs - Aryal, Narayan Prasad; Shah, Sarita Kumari; Dhakal, Anisha (Nepalese Journal of Business and Management Studies, 2023)
Despite the fact that many women hold leadership positions, there has been limited research on the factors influencing leadership positions among female entrepreneurs. Thus, the purpose of this study is to delve into the numerous factors, namely, gender stereotypes, career growth, and economic constraints that affect leadership positions across family support, among women entrepreneurs residing in Ward 4 of Kathmandu Metropolitan City. The study is guided by a quantitative research approach that involves descriptive, causal, and relational design. The described data were gathered from 102 respondents using a structured questionnaire. The data were analysed using IBM SPSS version 20 with various tools, such as the mean, median, standard deviation, variance, independent sample t-test, correlation, and regression. According to the study, there is a positive relationship between gender stereotypes, career growth, economic constraints, and leadership positions among women entrepreneurs, implying that women who are treated equally by society, who are self determined, and who are focused on achieving higher goals are more likely to achieve a leadership position. Similarly, family support made a significant difference for women who aspire to be leaders. The study revealed that gender stereotypes, career growth, and economic constraints all had a significant and positive impact on women entrepreneurs' leadership positions.